Digital Dynamic Marketing Capabilities in Green Hospitality: A Systematic Literature Review in the Emerging Countries Context - Sianipar, Ardin; Angelia, Widya; Abdau, Abrar (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Abstract This Systematic Literature Review (SLR) examines the role of Digital Dynamic Marketing Capabilities (DDMC) in advancing green Hospitality within emerging countries, addressing a critical gap at the intersection of digital innovation and sustainability. Guided by the dynamic capabilities framework, the study synthesizes 42 peer-reviewed studies from 2010 to 2025, sourced from databases such as Scopus, Web of Science digital infrastructure. Barriers, such as financial constraints and digital literacy gaps, pose challenges, particularly in rural areas. Outcomes encompass reduced carbon footprints, cost efficiencies, and improved customer loyalty, though benefits vary by context. The study contributes to dynamic capabilities theory by highlighting contextual moderators in emerging economies and offers practical insights for hospitality managers to leverage cost-effective digital tools for sustainability. Policymakers can support the adoption of DDMC by enhancing digital infrastructure and offering incentives. Gaps in the literature, including a limited focus on rural settings and emerging technologies such as blockchain, suggest avenues for future research. This SLR underscores DDMC’s transformative potential in fostering sustainable Hospitality in emerging markets.